Volumetric microleakage assessment of glass-ionomer-resin composite hybrid materials - De Magalhães, Cláudia Silami; Serra, Mônica Campos; Rodrigues Jr., Antônio Luiz (My University, 1999)
Objective: This study was intended to quantify the marginal leakage of three glass-ionomer-resin composite hybrid materials and compare it with the leakage exhibited by a glass-ionomer cement and a bonded resin composite system. Method and materials: Standardized Class V cavities were prepared on root surfaces of 105 extracted human teeth, randomly assigned to five groups of 21 each, and restored with either Ketac-Fil Aplicap, Z100/Scotchbond Multi-Purpose Plus, Vitremer, Photac-FH Aplicap, or Dyract. The teeth were thermally stressed for 500 cycles and stained with methylene blue. The microleakage was quantified spectrophotometrically, and the data were statistically analyzed with Friedman's test. Results: There were no significant differences in microleakage among the five groups. Restorations of all tested materials showed some marginal leakage in Class V cavities. Conclusion: The microleakage performance of glass-ionomer-resin composite hybrid materials was similar to those of a conventional glass-ionomer and a bonded resin composite system.
Keywords: Class V cavity; Glass-ionomer cement; Glass-ionomer-resin composite hybrid material; Marginal leakage; Resin composite; Volumetric microleakage